USUL FIKIH DALAM HUKUM ISLAM PROGRESIF - Yusdani, Yusdani (Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu, 2015)
Ushûl Fiqh in Progressive Islamic Law. The present article is aimed at describing though of ushûl fiqhwhich becomes a basis of progressive Islamic law. Basically, the progressive Islamic law has a basic concept ofushûl fiqh setting out ijtihad based contextual concept that comes from the essential of Islamic basic values(maqâsid as-syarî’ah). Its essential values such as justice, equity, and equality are transformed to respond thecontemporary humanity issues including democracy, human rights, gender equality, the rights of minorities, therelationship between religion and state, culture, science, and technology. Hence, the concept of progressiveushûl fiqh will develop and offer more humane Islamic law (anthropocentric transformative) than before byupholding the prophetical values. The framework can create some various field in Islamic such as cultural Islamic,interfaith Islamic law, political Islamic law, govermental Islamic law, environmental Islamic law, and multiculturalIslamic law.